Plasma levels of apolipoprotein A1 in malaria-exposed primigravidae are associated with severe anemia. - David C Simpson; Edward Kabyemela; Atis Muehlenbachs; Yuko Ogata; Theonest K Mutabingwa; Patrick E Duffy; Michal Fried (PLoS ONE, 2010)
Plasmodium falciparum placental malaria (PM) contributes to 10,000 maternal deaths due to severe anemia (SA) each year in Africa, primarily among primigravid women who are most susceptible. Increased levels of proinflammatory cytokines like TNF-alpha are associated with maternal anemia in first time mothers but not in other women. Here we aimed to identify additional changes in the plasma proteome associated with pregnancy malaria that may contribute to the development of malaria-related maternal anemia.A semi-quantitative mass spectrometry approach was used to compare the relative abundance of plasma proteins in anemic versus non-anemic women with PM. Levels of 24 proteins differed significantly between anemic and non-anemic primigravidae, including several lipid metabolism proteins and molecular transport proteins involved in the acute phase response signaling network. These differences were not observed in multigravid women who enjoy specific immunity that protect them from PM. In a confirmatory study of a larger cohort of primigravid women, levels of the lipid metabolism protein Apolipoprotein (Apo)-AI were significantly lower in PM+ women with SA.Apo-AI levels are significantly lower in severely anemic primigravidae with PM, and ApoA1 levels positively correlate with hemoglobin levels in primigravid but not multigravid women. Apo-AI is known to have anti-inflammatory effects, and thus Apo-AI reductions may contribute to the inflammatory processes that result in SA.